Sedating Mechanically Ventilated COVID-19 Patients with Volatile Anesthetics: Insights on the Last-Minute Potential Weapons - Aiman Suleiman; Abdallah Barjas Qaswal; Mazen Alnouti; Moh'd Yousef; Bayan Suleiman; Mohammad El Jarbeh; Ghadeer Alshawabkeh; Isam Bsisu; Abeer Santarisi; Muaweih Ababneh (MDPI AG, 2021)
Coronavirus Disease 2019 (COVID-19) has spread globally with the number of cases exceeding seventy million. Although trials on potential treatments of COVID-19 Acute Respiratory Distress Syndrome (ARDS) are promising, the introduction of an effective therapeutic intervention seems elusive. In this review, we explored the potential therapeutic role of volatile anesthetics during mechanical ventilation in the late stages of the disease. COVID-19 is thought to hit the human body via five major mechanisms: direct viral damage, immune overactivation, capillary thrombosis, loss of alveolar capillary membrane integrity, and decreased tissue oxygenation. The overproduction of pro-inflammatory cytokines will eventually lead to the accumulation of inflammatory cells in the lungs, which will lead to ARDS requiring mechanical ventilation. Respiratory failure resulting from ARDS is thought to be the most common cause of death in COVID-19. The literature suggests that these effects could be directly countered by using volatile anesthetics for sedation. These agents possess multiple properties that affect viral replication, immunity, and coagulation. They also have proven benefits at the molecular, cellular, and tissue levels. Based on the comprehensive understanding of the literature, short-term sedation with volatile anesthetics may be beneficial in severe stages of COVID-19 ARDS and trials to study their effects should be encouraged.